The peculiarity of the psychological health of people who regularly attend dance classes - Baranova, Elvira Avksentevna (Razvitie obrazovaniâ (Online), 2024)
The article is devoted to the problem of studying the psychological health of adults. A review of the main works revealing approaches to understanding psychological health as a phenomenon is carried out, a number of scientific papers illustrating the characteristic features of psychological health of persons in different fields and types of activity (students, teachers, medical and social workers, representatives of the Ministry of Internal Affairs system, etc.) are analyzed. The current shortage of knowledge in science regarding psychological health of people who regularly practice dancing. The article also presents the results of a study that describes the peculiarities of the psychological health of people (average age 48 years) who regularly attend dance classes (folk, ballroom, dance vibroplasty).